STEREOTIP MASYARAKAT TERHADAP LAKI-LAKI YANG BEROLAHRAGA CHEERLEADER - Rahfalia Zaenh (2021)
The study aims to explain the negative stereotypes that society has about men who cheerleader and to find out the reasons for giving these negative stereotypes. Research is based on symbolic interaction, stereotype, and gender stereotype.The research uses a descriptive qualitative. The informants in this study consisted of seven men or women aged 19 to 29 years who live in Jakarta and are also included in the research criteria. The results of this study found that the negative stereotypes given by society to men who cheerleader are feminine men, flamboyant men and have sexual deviation. the negative stereotypes, it turns out is also generalized by society to all men who choose cheerleader as their sport. The reasons for giving this negative stereotypes because the interactions made by informants with men who cheerleader, where the informants catch symbols likes as facial gestures, body, how to walk, dresses and speak are considered different from normal men in general. The informant said that the culture of masculinity supported their judgment when they saw the symbols shown by man who cheerleader. In addition, it was also revealed that another factor are like environment of friendship, personal experience and media also influenced them to giving these negative stereotypes to men who cheerleader